Development of a software application for teaching computer networking - Tan, Xing Huan (Nanyang Technological University, 2021)
Computer networking is a broad subject of study, with many levels of abstraction and protocols that students have to learn, typically over a period of several semesters. Appropriate use of software in tandem with traditional textbooks and lectures can deepen students’ understanding of the course material, and enhance the learning experience. In this project, a web application with interactive elements and animations will be created. The application will allow learners to explore Dijkstra’s algorithm, which is taught as part of computer networking courses, and visualise how the algorithm runs step-by-step in a web browser. This would give students an additional level of understanding beyond the textbook for this topic. The application will be designed with a user-centric approach, developed with modern web technologies, and deployed on the Internet, ensuring that as many students as possible will be able to access and make use of it as a learning aid. This report details the design and implementation of the web application, including an initial interest survey, software requirement specifications, and iterative software development and usability testing of the application. This report will also discuss certain challenges faced during development, as well as documentation and suggested improvements for future developers.